Tuberculosis extrapulmonar y diabetes mellitus tipo 2 en pacientes del Hospital Regional de Loreto 2018-2023 - Rengifo Peña, Andy (2025)
GENERAL OBJECTIVE: To determine the relationship between extrapulmonary tuberculosis and type 2 diabetes mellitus at the Loreto Regional Hospital during the period 2018-2023. MATERIALS AND METHODS: Quantitative and cross-sectional study. The population will be all patients hospitalized between 2018 and 2023 with Extrapulmonary Tuberculosis in the infectious disease service of the Regional Hospital of Loreto. The characteristics of the study will be presented in percentages and tables or measures for quantitative data. Contingency analysis will use test of proportions. SPSS v25 will be used. CONCLUSIONS: The characteristics associated with extrapulmonary tuberculosis in patients with diabetes mellitus are related to personal history, family history and other risk events at the Regional Hospital of Loreto.